Phospho-Ser727 triggers a multistep inactivation of STAT3 by rapid dissociation of pY705–SH2 through C-terminal tail modulation. (14th October 2019) - Yang, Junhao; Kunimoto, Hiroyuki; Katayama, Bumpei; Zhao, Hong; Shiromizu, Takashi; Wang, Lingyu; Ozawa, Toshiyuki; Tomonaga, Takeshi; Tsuruta, Daisuke; Nakajima, Koichi
Abstract : How pS727 regulates STAT3 activation-inactivation cycles Abstract: Signal transducer and activator of transcription 3 (STAT3) is involved in many biological processes, including immunity and cancer. STAT3 becomes phosphorylated at Tyr705 and Ser727 on IL-6 stimulation. Phospho-Tyr705 (pY705) stabilizes the STAT3 dimer with reciprocal interactions between pY705 and the SH2 of the other molecule and phospho-Ser727 (pS727) accelerates pY705 dephosphorylation. We study how pS727 regulates STAT3 in both structural and biological perspectives. Using STAT3 reconstituted in HepG2-stat3-knockout cells, we show that pS727, together with a handshake N-terminal domain (NTD) interaction, causes rapid inactivation of STAT3 for pY705 dephosphorylation and a chromosome region maintenance 1 (CRM1)-independent nuclear export, which is critical for faithful STAT3 response to the cellular signals. The various N-terminal tags, GFP-related Ruby and FLAG, rendered the export CRM1-dependent and especially FLAG-tag caused nuclear accumulation of STAT3, indicating the presence of conformational changes in inactivation. Impaired reactivation of STAT3 by S727A or FLAG-tag delayed or inhibited the IL-6-induced saa1 mRNA expression, respectively. The detailed analysis of the pY705–SH2 structure identified the C-terminal tail (CTT) from L706 to P715 as a key regulator of the CTT–CTT intermolecular and the CTT–SH2 intramolecular interactions that support pY705–SH2 association. The functional studies using multiple STAT3 mutants indicated that the degree of the two interactions determines the stability of pY705–SH2 interaction. Importantly, Pro715 was critical for the pS727's destabilizing activity and the known phosphorylation and acetylation at the CTT structurally inhibited the pY705–SH2 interaction. Thus, pS727 triggers pY705–SH2 dissociation by weakening the supportive interactions likely through CTT modulation, inducing rapid cycles of STAT3 activation–inactivation for proper function of STAT3.